Analisis perhitungan penyusutan aset tetap dalam rangka memenuhi kewajiban perpajakan pada PT. IR Struktur Papua - Kiling, Jessica Natalia; Warongan, Jessy D.L.; Weku, Priscillia (Yayasan Widyantara Nawasena Raharja, 2024)
This research aims to find out how the calculation of depreciation of fixed assets in order to fulfill tax obligations is in accordance with Law No.7 of 2021 and to find out how tax planning uses the fixed asset depreciation method for tax payments by PT. IR Structure of Papua. The type of research used is descriptive qualitative, namely by describing and analyzing existing situations and problems, especially regarding depreciation of fixed assets. The research results show that PT. IR Structure Papua uses the straight-line method in calculating depreciation of fixed assets, but this method cannot help in minimizing tax payments. Based on the calculations that have been carried out, if the company uses the declining balance method, it results in a greater depreciation expense so that the resulting tax will be lower. In tax planning, the declining balance method is more appropriate in minimizing income tax payments in the initial year of depreciation so that the company can make tax savings for other operational activities of the company. So, it is known that companies need to change depreciation methods so that tax planning in minimizing tax payments can be more effective.